Bullying at school and its impact on mental and physical condition of a child - Machová, Alena; Boledovičová, Mária (Journal of Nursing, Social Studies and Public Health, 2014)
The concept of social determinants of health is the most complex approach to the analysis of personal health status and is based on the definition provided by the World Health Organization in 1948. The following are the ten social determinants: social gradient, stress, childhood, social inclusion, social support, employment, unemployment, nutrition, addiction and transport. The goal of this qualitative research survey was to map the influence of selected social determinants to the health of the child. The goal of this article is to deal especially with the social determinant of social exclusion in relationship to school attendance, namely, bullying and its influence on the physical and mental state of children. The target group consisted of families with children from the South Bohemia region. Ten married couples and an unmarried couple with a total number of 21 children, the eldest one being 23, and the youngest only 3 years old. 13 girls and 8 boys were targeted. The data were collected via a method of using a direct inquiry technique which involved in-depth interviews with mothers of school-aged children, followed by direct transcription and open coding analysis with a pen and paper technique. The results showed that from 11 families, only two experienced bullying and one child had negative impact on his mental and physical condition as a result of being bullied.
Keywords: Research; Female; rodina; dítě; Social Class; šikana; ženské pohlaví; nemoc; Adolescent; výzkum; interpersonální vztahy; lidé; Bullying; sběr dat; Disease; školy; Schools; sociální přizpůsobení; Social Adjustment; Male; Data Collection; Internet; společenská třída; Family; Child; Social Behavior; Interpersonal Relations; mužské pohlaví; sociální chování; internet; mladiství; Humans